2014
DOI: 10.1002/chem.201404362
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective CH Borylations of Cyclopropanes and Cyclobutanes with Silica‐Supported Monophosphane–Ir Catalysts

Abstract: Heteroatom-directed C-H borylation of cyclopropanes and cyclobutanes was achieved with silica-supported monophosphane-Ir catalysts. Borylation occurred at the C-H bonds located γ to the directing N or O atoms with exceptional cis stereoselectivity relative to the directing groups. This protocol was applied to the borylation of a tertiary C-H bond of a ring-fused cyclopropane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 67 publications
0
36
0
Order By: Relevance
“…Very interestingly, we found that the C À H borylation proceeded in a cis-selective manner, which is opposite to the finding of Liskey and Hartwig for cyclo-propane CÀH borylation (steric-controlled, trans-selective). [13] Possible modes of action for the pivaloylamide directing effect might be worth mentioning. [12] It should be noted that the group of Sawamura recently reported a heteroatom-directed cis-selective CÀH borylation of cyclopropanes by silica-supported monophosphine iridium catalysts.…”
Section: -Arylcyclopropylamines (Acpas) Have Received Muchmentioning
confidence: 99%
“…Very interestingly, we found that the C À H borylation proceeded in a cis-selective manner, which is opposite to the finding of Liskey and Hartwig for cyclo-propane CÀH borylation (steric-controlled, trans-selective). [13] Possible modes of action for the pivaloylamide directing effect might be worth mentioning. [12] It should be noted that the group of Sawamura recently reported a heteroatom-directed cis-selective CÀH borylation of cyclopropanes by silica-supported monophosphine iridium catalysts.…”
Section: -Arylcyclopropylamines (Acpas) Have Received Muchmentioning
confidence: 99%
“…Despite their synthetic versatility,t here are no examples of enantioselective catalytic methods for their preparation in the literature. [9] The only two examples reported for the synthesis of enantiomerically enriched cyclobutyl boronic esters require the use of stoichiometric amounts of ac hiral inductor and are structurally limited. [10] Therefore,t he development of ag eneral catalytic enantioselective method is highly desirable.W e envisioned using ac yclobutene,achiral copper(I) complex and ad iboron compound to accomplish this goal.…”
mentioning
confidence: 99%
“…Based on the previousreport [5] and the signal of the 11 BNMR spectrum, [16] the intramolecular coordination of the carbonyl oxygen to the Ba tom (G)m ay disturbt he binding of the Ru center to the carbonyl (H or I), which will lead to the failure in bisborylation processes at the second N-ethyl group of amides or ureas. This suggestst hat the exclusive selectivity in the C(sp 3 )ÀHm onoborylation of amides is likely.…”
mentioning
confidence: 98%
“…[3] Despite the impressive achievementsi nb orylation processes, the selectiveb orylation of C(sp 3 )ÀHb onds in unactivated carboxamides still poses challenges and mainly concerns the use of catalysts ystems based on the noblemetals Rh and Ir. [5] This work representedabreakthrough in the borylation of N-adjacent C(sp 3 )ÀHb onds in carboxamides, but the substrate scope was restricted to alkyl amides. [5] This work representedabreakthrough in the borylation of N-adjacent C(sp 3 )ÀHb onds in carboxamides, but the substrate scope was restricted to alkyl amides.…”
mentioning
confidence: 99%
See 1 more Smart Citation